Telemedicine – medicine and technology in fight for our health - Zubrzycki, Jarosław; Małecka-Massalska, Teresa (Polish Journal of Public Health, 2010)
Telemedicine is a developing area in medicine. The use of computer technology has increased rapidly in the last decade. This is exemplified by the trends in telemedicine. This paper discusses the history and the development of telemedicine. Specific topics include telepathology, emergency and home health care telemedicine.